MiR-454-3p Promotes Oxaliplatin Resistance by Targeting PTEN in Colorectal Cancer - Qian, Xiao-Lan; Zhou, Fang; Xu, Song; Jiang, Jian; Chen, Zhi-Peng; Wang, Shao-Kai; Zuo, Yun; Ni, Chen (Frontiers in Oncology, 2021)
Colorectal cancer is one of the most common malignancies worldwide. Oxaliplatin is the first-line chemotherapeutic agent for the treatment of advanced colorectal cancer. However, acquired resistance to oxaliplatin limits its therapeutic efficacy, and the underlying mechanism remains largely unclear. In this study, we compared the expression of a panel of microRNAs (miRNAs) between oxaliplatin-sensitive and -resistant HCT-116 colorectal cancer cells. We found that miR-454-3p was significantly up-regulated in oxaliplatin-resistant cells and was the most differently expressed miRNA. Interestingly, we observed that inhibition of miR-454-3p resensitized resistant cells to oxaliplatin and enhanced oxaliplatin-induced cellular apoptosis. Moreover, we determined that miR-454-3p promoted oxaliplatin resistance through targeting PTEN and activating the AKT signaling pathway. In vivo study revealed that overexpression of miR-454-3p decreased the sensitivity of HCT-116 xenograft tumors to oxaliplatin treatment in a mouse model. Clinically, overexpression of miR-454-3p was associated with decreased responsiveness to oxaliplatin-based chemotherapy, as well as a short progression-free survival. Taken together, our study indicated that the expression of miR-454-3p could be used to predict oxaliplatin sensitivity, and targeting miR-454-3p could overcome oxaliplatin resistance in colorectal cancer.